Perancangan Film Animasi 3D Bertema Islami Berjudul “Sedekah itu Indah” Menggunakan Metode Pose-to-Pose - Anjar Dwimursito; Juniardi Nur Fadilah; Fresy Nugroho (Jurnal Informatika dan Teknologi Komputer (J-ICOM), 2022)
3D Animated Film is one type of film that is in great demand by various age groups, both teenagers, old people and children. The appearance is attractive and the presentation of a light storyline is an attraction. Many of the animated films tell funny things, history, to stories that are educational and contain moral messages. Messages in animated films are usually presented lightly, so the message to be conveyed becomes easier to capture. Therefore, apart from functioning as a medium of entertainment, animated films are also often used as a means of education, one of which is the education of Islamic values. The purpose of this research is to educate and provide information about our obligation to help each other among religious people. As for this research, a 3D animated film is made which tells us that if we meet someone who needs help, we as Muslims are obliged to help him. Making this 3D animation using Blender software, which is an open source software and can be downloaded directly on the official Blender website. The method I use in making this 3D animation is the Pose-to-Pose method. This method will determine the key poses called keypose on the movement, so that the 3D animation movement becomes easier. The design of 3D animated films made in this study is expected to produce an animated film that can educate the audience so that they can take the moral message presented, from the story entitled "Sedekah is Beautiful".